Penegakan Hukum Terhadap Pelaku Tindak Pidana Kekerasan Dalam Rumah Tangga (Studi Penelitian Pada Polrestabes Medan) - Syarifuddin Syarifuddin (Universitas Islam Sumatera Utara, 2021)
The purpose of law enforcement is to harmonize the relationship of the values that are outlined in the rules, and to create, maintain and preserve peace in social life. Women and children are very vulnerable to becoming victims in all forms of violence or criminal acts, including violence in the domestic sphere. This research is descriptive analysis because it only explains about legal arrangements, law enforcement, as well as barriers and efforts to enforce the law by Medan Police against perpetrators of criminal acts of domestic violence (Research Study at Medan Police).The regulation of domestic violence law is contained in the Article 4 of Law of the Republic of Indonesia Number 23 of 2004 concerning Domestic Violence which states that the purpose of domestic violence is to prevent all forms of domestic violence, protect victims, take action against perpetrators, and maintain the integrity of the household. The application of the law by the police against the perpetrators of criminal acts of domestic violence prioritizes prevention, protection of victims, and maintaining household integrity. Barriers and efforts in law enforcement are that the regulations contained in PKDRT Law have not been integrated with other statutory regulations for law enforcement against criminal acts of domestic violence, so that the police strive to deal with restorative justice in order to improve and maintain the integrity of the households of the people dealing with the law.Keywords: Law Enforcement, Perpetrator, Criminal Acts, Domestic Violence